2002
DOI: 10.2307/3060982
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Implementation of Recovery Plans

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Wiley is collaborating with JSTOR to digitize, preserve and extend access to Ecological Applications This content downloaded from 129.81.226.78 on Wed, 06 Apr 2016 17:01:35 UTC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…Allocation toward the least funded species (e.g., the 38% of taxa receiving <$5000) is clearly inadequate for recovery management and task accomplishment. Supporting this contention, Lundquist et al (2002) report that most recovery tasks for most species remain unaccomplished. Allocation at the upper end of expenditures is more difficult to assess.…”
Section: Recovery Expendituresmentioning
confidence: 76%
See 1 more Smart Citation
“…Allocation toward the least funded species (e.g., the 38% of taxa receiving <$5000) is clearly inadequate for recovery management and task accomplishment. Supporting this contention, Lundquist et al (2002) report that most recovery tasks for most species remain unaccomplished. Allocation at the upper end of expenditures is more difficult to assess.…”
Section: Recovery Expendituresmentioning
confidence: 76%
“…DeShazo & Freeman (2006) demonstrate a clear link between recovery funding and congressional representation on the relevant oversight committees. In a related study, Lundquist et al (2002) found that species listed by the FWS with a conflict designation have much more of their recovery plan tasks accomplished. This latter assessment suggests that despite politics, or maybe because of it, species in conflict get more recovery attention.…”
Section: Recovery Expendituresmentioning
confidence: 95%
“…Wider use of threatened-species recovery teams is one way that managers can coordinate and prioritise issues, projects and actions, and potentially alleviate some issues with the predominance of small-scale actions. The importance of building partnerships for improving recovery outcomes has been discussed earlier, and the benefits of having a recovery team or coordinator for improving cross-jurisdictional coordination and species-recovery trajectory have been identified elsewhere (Lundquist et al 2002;Lintermans 2013b). Since the early 2000s, there has been no national funding available for establishment or operation of national recovery teams (Lintermans 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Recovery plans can be effective at reducing threats for individual species in particular locations, but they are not designed to reduce widespread threats from industries. Additionally, plans often take years to be developed and implemented, and these lengthy delays can result in continued species declines, leading to increased costs and decreased likelihood of successful recovery (Lundquist et al 2002). Proactive, broad-scale measures to reduce threats across multiple species outside of the recovery planning framework are therefore needed to lower financial costs and halt species declines (Bloomgarden 1995;Scott et al 2005).…”
Section: Introductionmentioning
confidence: 99%